2007
DOI: 10.1177/014556130708600603
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic View of a Long-term Inferior Meatal Antrostomy

Abstract: A 70-year-old man sought treatment for postnasal drainage. He had undergone sinus surgery 33 years earlier. At that time, infer~or meatal antrostomies were performed without stripping of the maxillary sinus mucosa. The natural ostia of the maxillary sinuses and the uncinate processes had not been disturbed. Postoperatively, the patient appeared clinically to have satisfactorily functioning sinuses with adequate drainage and ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Dependent drainage through an inferior antrostomy may benefi t patients with disturbed mucociliary transport-for example, patients with cystic fi brosis. 7 Th e long-term eff ects of meatal antrostomy were discussed recently by Yanagisawa et al 7 Our study showed that intramaxillary sinus pressures along the nasal cavity-maxillary sinus exchange routes were greater when the patency of the natural ostia was augmented by counteropening. Th e pressures were better during rapid breathing than quiet breathing.…”
Section: Discussionsupporting
confidence: 52%
“…Dependent drainage through an inferior antrostomy may benefi t patients with disturbed mucociliary transport-for example, patients with cystic fi brosis. 7 Th e long-term eff ects of meatal antrostomy were discussed recently by Yanagisawa et al 7 Our study showed that intramaxillary sinus pressures along the nasal cavity-maxillary sinus exchange routes were greater when the patency of the natural ostia was augmented by counteropening. Th e pressures were better during rapid breathing than quiet breathing.…”
Section: Discussionsupporting
confidence: 52%
“…Nevertheless, endoscopic approach via inferior meatal antrostomy has the advantage of inferior meatal naso-antral window that avoids violation of the ostiomeatal complex (OMC) and provides better access to anterior-inferior maxillary sinus lesions. Arguments against inferior meatal antrostomy include: persistent sinus disease following surgery, low patency rates, possible injury to the nasolacrimal duct or to developing canine teeth, and technical difficulties associated with the procedure [24,25]. While these arguments were substantial using anterior rhinoscopy approach, they are not valid with endoscopic approach in EIMA.…”
Section: Endoscopic Inferior Meatal Antrostomy (Eima)mentioning
confidence: 99%
“…The lesion is then removed with straight and curved instruments. At the end of the procedure, the inferior turbinate is lateralized back to its original position [24,25].…”
Section: Endoscopic Inferior Meatal Antrostomy (Eima)mentioning
confidence: 99%